Answer:
x = 17
Step-by-step explanation:
-1 is the same as minus-ing it by 1.
10 + x - 1 = 26.
10 + 16 - 1 = 25, so it must not be x = 16.
x = 17. lets try it.
10 + 17 - 1 = 26!!
Answer:
Step-by-step explanation:
<u>Use the interest formula:</u>
- I = Prt, where P - amount of loan, r- interest rate, t- time in years
<u>Robert:</u>
- I = 30000*(4.9/100)*4 = 5880
<u>Susan:</u>
- I = 30000*(4.5/100)*6 = 8100
<u>Difference in amounts of interest:</u>
Susan paid $2220 more
Answer:
next should be 2250 if my math is correct
<h3>
Answer: Choice A</h3>
![x^2\left(\sqrt[4]{x^2}\right)](https://tex.z-dn.net/?f=x%5E2%5Cleft%28%5Csqrt%5B4%5D%7Bx%5E2%7D%5Cright%29)
=====================================================
Explanation:
The fourth root of x is the same as x^(1/4)
I.e,
![\sqrt[4]{x} = x^{1/4}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%7D%20%3D%20x%5E%7B1%2F4%7D)
The same applies to x^10 as well
![\sqrt[4]{x^{10}} = \left(x^{10}\right)^{1/4}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%5E%7B10%7D%7D%20%3D%20%5Cleft%28x%5E%7B10%7D%5Cright%29%5E%7B1%2F4%7D)
Multiply the exponents 10 and 1/4 to get 10/4
![\sqrt[4]{x^{10}} = \left(x^{10}\right)^{1/4} = x^{10*1/4} = x^{10/4}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%5E%7B10%7D%7D%20%3D%20%5Cleft%28x%5E%7B10%7D%5Cright%29%5E%7B1%2F4%7D%20%3D%20x%5E%7B10%2A1%2F4%7D%20%3D%20x%5E%7B10%2F4%7D)
![\sqrt[4]{x^{10}} = x^{10/4}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%5E%7B10%7D%7D%20%3D%20x%5E%7B10%2F4%7D)
-----------------------
If we have an expression in the form x^(m/n), with m > n, then we can simplify it into an equivalent form as shown below
![x^{m/n} = x^a\sqrt[n]{x^b}](https://tex.z-dn.net/?f=x%5E%7Bm%2Fn%7D%20%3D%20x%5Ea%5Csqrt%5Bn%5D%7Bx%5Eb%7D)
The 'a' and 'b' are found through dividing m/n
m/n = a remainder b
'a' is the quotient, b is the remainder
-----------------------
The general formula can easily be confusing, so let's replace m and n with the proper numbers. In this case, m = 10 and n = 4
m/n = 10/4 = 2 remainder 2
We have a = 2 and b = 2
So
![x^{m/n} = x^a\sqrt[n]{x^b}](https://tex.z-dn.net/?f=x%5E%7Bm%2Fn%7D%20%3D%20x%5Ea%5Csqrt%5Bn%5D%7Bx%5Eb%7D)
turns into
![x^{10/4} = x^2\sqrt[4]{x^2}](https://tex.z-dn.net/?f=x%5E%7B10%2F4%7D%20%3D%20x%5E2%5Csqrt%5B4%5D%7Bx%5E2%7D)
which means
![\sqrt[4]{x^{10}} = {x^2} \sqrt[4]{x^2}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7Bx%5E%7B10%7D%7D%20%3D%20%7Bx%5E2%7D%20%5Csqrt%5B4%5D%7Bx%5E2%7D)